Fast and Selective Semihydrogenation of Alkynes by Palladium Nanoparticles Sandwiched in Metal–Organic Frameworks. Issue 9 (21st January 2020) - Choe, Kwanghak; Zheng, Fengbin; Wang, Hui; Yuan, Yi; Zhao, Wenshi; Xue, Guangxin; Qiu, Xueying; Ri, Myonghak; Shi, Xinghua; Wang, Yinglong; Li, Guodong; Tang, Zhiyong
Abstract: The semihydrogenation of alkynes into alkenes rather than alkanes is of great importance in the chemical industry. Unfortunately, state‐of‐the‐art heterogeneous catalysts hardly achieve high turnover frequencies (TOFs) simultaneously with almost full conversion, excellent selectivity, and good stability. Here, we used metal–organic frameworks (MOFs) containing Zr metal nodes ("UiO") with tunable wettability and electron‐withdrawing ability as activity accelerators for the semihydrogenation of alkynes catalyzed by sandwiched palladium nanoparticles (Pd NPs). Impressively, the porous hydrophobic UiO support not only leads to an enrichment of phenylacetylene around the Pd NPs but also renders the Pd surfaces more electron‐deficient, which leads to a remarkable catalysis performance, including an exceptionally high TOF of 13835 h −1, 100 % phenylacetylene conversion 93.1 % selectivity towards styrene, and no activity decay after successive catalytic cycles. The strategy of using molecularly tailored supports is universal for boosting the selective semihydrogenation of various terminal and internal alkynes. Abstract : Metal–organic frameworks (MOFs) with Zr metal nodes ("UiO") with tunable wettability and electron‐withdrawing ability were employed as activity accelerators for the semihydrogenation of alkynes catalyzed by sandwiched palladium nanoparticles. The use of this support leads to full conversion, excellent selectivity, and good catalyst stability.